Paleomagnetism of Paleogene rocks of the Central—East Kamchatka and Komanorsky Islands: tectonic implications (Dataset) ... - M.L. Bazhenov; V.S. Burtman; O.A. Krezhovskikh; M.N. Shapiro (Magnetics Information Consortium (MagIC), 2006)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Paleomagnetism of Paleogene rocks of the Central—East Kamchatka and Komanorsky Islands: tectonic implications ...